2022
DOI: 10.1021/acs.orglett.2c02747
|View full text |Cite
|
Sign up to set email alerts
|

Multiselective Diels–Alder Reaction of α-Arylacroleins Catalyzed by Boron Tribromide-Assisted Chiral Phosphoric Acids

Abstract: A multiselective Diels−Alder (DA) reaction of α-arylacroleins with cyclopentadiene using BBr 3 -assisted chiral BINOL-derived phosphoric acid catalysts has been developed. This unusual exo-and enantioselective DA reaction can be multicontrolled by the chiral cavity of the in situ-formed acid−base cooperative catalysts, in particular, suppressing the competitive hetero Diels−Alder (HDA) reaction effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…UV–vis (CH 2 Cl 2 ) λ max (ε) = 239 nm (3879 M –1 cm –1 ). The data obtained matched those reported in the literature …”
Section: Methodssupporting
confidence: 86%
See 3 more Smart Citations
“…UV–vis (CH 2 Cl 2 ) λ max (ε) = 239 nm (3879 M –1 cm –1 ). The data obtained matched those reported in the literature …”
Section: Methodssupporting
confidence: 86%
“…The data obtained matched those reported in the literature. 22 General Procedure for the Photoinduced Reactions. A solution of the α,β-unsaturated carbaldehyde in dry CH 2 Cl 2 (1.5 mL) was transferred to a Duran phototube.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of cyclic alkenes as dienophile partners in a Diels–Alder cycloaddition reaction provides a very straight-forward strategy to access fused skeletons; however, cis -fused products are usually obtained due to the inherent concerted reaction mechanism. 9 As illustrated in Scheme 1b , exclusive endo -selectivity was observed in the uncatalysed inverse-electron-demand Diels–Alder reaction between 1,3-cyclohexadiene 1a and aurone-derived 1-azadiene 2a, 10 resulting in the formation of cis -fused polycyclic product 3a in a moderate yield after heating the reaction mixture at 80 °C for 36 h. Recently, our group demonstrated that Pd 0 could act as a π-Lewis base catalyst to increase the highest occupied molecular orbital (HOMO) energy of linear 1,3-dienes through η 2 -coordination, thus promoting asymmetric Friedel–Crafts-type vinylogous addition to N -sulfonylimines enantioselectively. 11 We envisaged that the Pd 0 -π-Lewis base catalysis would facilitate the asymmetric assembly of 1,3-cyclohexadiene 1a and 1-azadiene 2a by generating the high-HOMO-energy complex I.…”
Section: Introductionmentioning
confidence: 99%